Laparoscopic vs. open portoenterostomy for biliary atresia: a meta-analysis of pediatric surgical outcomes - Zhu, Jie; Wu, Bin; Cai, Peng; Pan, Jiang; Zhu, Zhenwei (Frontiers in Pediatrics, 2024)
Background: The pivotal importance of surgical treatment for pediatric biliary atresia is well-established. This systematic review and meta-analysis was designed to assess the comparative efficacy and safety of open portoenterostomy (OPE) and laparoscopic portoenterostomy (LPE) in managing this condition, providing valuable guidance for clinical decision-making. Methods: A comprehensive literature review was conducted by two researchers in databases such as PubMed, up to July 10, 2024, focusing on studies that evaluated the role of LPE versus OPE. Data analysis was performed utilizing the RevMan 5.4 software suite. Results: The meta-analysis incorporated findings from 15 studies involving a total of 964 pediatric patients with biliary atresia. LPE was associated with decreased intraoperative blood loss [Mean Difference (MD) = -10.80, 95% Confidence Interval (CI) (-13.54, -8.05)] and shortened hospital stay [MD = -2.18, 95% CI (-3.69, -0.67)]. Conversely, the operative time for LPE was considerably longer when compared to OPE [MD = 35.45, 95% CI (26.17, 44.72)]. No significant disparities were noted in the postoperative jaundice clearance rate [Odds Ratio (OR) = 0.98, 95% CI (0.71, 1.35)], incidence of postoperative cholangitis [OR = 0.96, 95% CI (0.66, 1.39)], the rate of liver transplantation between the two surgical approaches [OR = 0.69, 95% CI (0.32, 1.48)], or 2-year survival of the native liver [OR = 1.10, 95% CI (0.67, 1.80)]. Conclusion: LPE offers more advantages over OPE, including diminished invasiveness and expedited recovery. These benefits suggest that LPE is an emerging and viable alternative in the clinical management of biliary atresia, warranting further investigation and consideration in surgical practice.